FREKUENSI SOIL TRANSMITTED HELMINTHS PADA MURID SEKOLAH DASAR NEGERI 31 PASIR KANDANG KECAMATAN KOTO TANGAH KOTA PADANG - Rahmadani, Diana; Indriati, Gustina; Lusi Zeswita, Amein (Pendidikan Biologi, 2013)
Intestinal helminth infections are transmitted via soil (Soil Transmitted Helminths) isstill a health problem facing society in Indonesia. The STH worms infect more children livingin slums and have poor sanitation. Elementary School is located at 31 Pasir Kandang lowlandcoastal areas that the average population has lower economic level and have inadequate toiletfacilities. Therefore research has been carried out with the aim to determine the frequency ofSoil Transmitted Helminths in Primary School Pupils Pasir Kandang 31 Sub Tangah KotoPadang. December 9, 2012 using descriptive methods.The study was conducted onDecember 2 The population in this study were students of SDN 31 Pasir Kandang as manyas 368 people. Sampling was done by random sampling of a population of 57 people. Stoolexamination conducted at the Laboratory of Biology Education Program STKIP PGRI WestSumatera by way of direct observation. The results showed that students of SDN 31 STHinfection as much as 59.65% with the percentage of each species from infected (20.59%Ascaris lumbricoides, Trichuris trichiura 14.71%, 5.88% hookworm, Ascaris lumbricoidesand Trichuris trichiura 35.29%, Trichuris trichiura and hookworm 2.94% after Ascarislumbricoides, Trichuris trichiura and hookworm 20.59%).